Statistical testing mediation in structural equations models variables with practical application - كمال, غفران اسماعيل; جاسم, بشرى سعد (Journal of Economics and Administrative Sciences, 2018)
In this research was the study of a single method of estimation and testing parameters mediating variables (Mediation) in a specimen structural equations SEM a bootstrap method, for the purpose of application of the integrated survey of the situation Marital data and health mirror Iraqi (I-WISH) for the year 2011 from the Ministry of Planning - device Central Bureau of Statistics, and applied to the appropriate data from the terms of the data to a form of structural equation SEM using factor analysis affirmative (Confirmatory Factor analysis) CFA As a way to see the match variables that make up the model, and after confirming the model matching or suitability are having the effect of variables mediation in the model tested by the bootstrap mentioned above using AMOS V.23 software method, as researcher found that the independent variable X affects the dependent variable Y indirectly through the mediation of one variable of the presence of any single mediation in the form.